Pulmonary disease burden in Hispanic and non‐Hispanic children with sickle cell disease. Issue 8 (11th June 2020) - Chen, Laura; Gong, Jacqueline; Matta, Esther; Morrone, Kerry; Manwani, Deepa; Rastogi, Deepa; De, Aliva
Abstract: Rationale: Pulmonary complications are the leading cause of morbidity and mortality in sickle cell disease (SCD) patients. Research in SCD has predominantly been conducted on African‐Americans, and the disease burden of SCD in other races and ethnicities, including Hispanic patients, is not well characterized. Objective: To compare pulmonary disease burden between Hispanic and non‐Hispanic ethnic groups among children with SCD. Methods: In a retrospective chart review on 566 SCD patients followed at the Children's Hospital at Montefiore, NY, we compared the pulmonary disease burden and disease management in Hispanic patients to their non‐Hispanic counterparts. We also compared the contribution of demographic and clinical variables to acute chest syndrome (ACS), vaso‐occlusive crisis (VOC), and hospitalizations for SCD related complications between the two ethnic groups. Results: Hispanic patients had a greater proportion of ACS, and had lower forced expiratory volume (FEV1), forced vital capacity, and vital capacity, compared to non‐Hispanics. Hispanic patients were more likely to be evaluated in pulmonary clinic and to be on inhaled corticosteroids, short‐acting β agonizts, and leukotriene receptor antagonists. In addition, Hispanic children were more likely to be on hydroxyurea, and receive exchange transfusions. However, the association of asthma with the proportion of ACS did not differ between Hispanics and non‐Hispanics. Conclusion: Hispanic children with SCD had differences in their pulmonary function profile and received more pulmonary evaluations than non‐Hispanic children.